Przemiany społeczno-kulturowe w okresie formowania się państwa piastowskiego w Wielkopolsce północno-zachodniej na podstawie materiałów archeologicznych z Santoka i Międzyrzecza - Zamelska-Monczak, Kinga (Folia Praehistorica Posnaniensia, 2018)
The strongholds of Santok and Międzyrzecz belong to major centers of the northwestern Great Poland in the period of formation the first Polish state. They were occupied in the same time but developed in entirely different conditions. The Santok stronghold is located on the borderland between Great Poland and Pomerania, at the place where two rivers – Warta and Noteć converge. A placement of the site within a communication net, in the border zone, and in a close proximity to the Baltic, facilitated contacts with distant regions leading to the development of strongholds in the Early Middle Ages. The stronghold was erected as a trade outpost in the 8th century. Archaeological excavations of different stratigraphic levels produced a very rich collection of artifacts originating from remote areas of the Baltic zone as well as eastern and southern Europe. This made possible to recognize subsequent phases of the settlement development and reflect on the role Santok played in the past. Międzyrzecz is situated on the Obra river in a long occupied area in western part of Great Poland. The stronghold was built in the first half of the 10th century. The analysis of the ceramic materials indicates that trajectory of pottery production departs from the developments reported for central Great Poland, but shows similarities to the Lower Lusatian region. This is indicative of connections among Slavic tribes inhabiting this region in the 9th century. In the following 10th century, Międzyrzecz was incorporated into the first Piast State and it became one of its most important centers of administration. The ramparts were rebuilt and widened. In the 11th century, the abbey was built near Międzyrzecz to facilitate missionary work among the pagan Slavs. The development of Santok and Międzyrzecz in the Early Middle Ages was determined by their placing in the very center of the communication net. The Piast dynasty attributed a defensive character to this part of the country, aimed at protecting its core from a military invasion coming from the west. These circumstances led eventually to the emergence and subsequent dynamic development of these cities.